Perbedaan Jumlah Trombosit dan Laktat Dehidrogenase pada Preeklampsia Berat Early Onset dengan Late Onset - Sita Nuraini; Bambang Abimanyu; Azma Rosida (Homeostasis, 2020)
Abstract: Preeclampsia is an emergency problem in the field of obstetrics which affects the well-being of mothers and babies. Based on its onset, preeclampsia is divided into early onset and late onset. The pathophysiology of preeclampsia is caused by endothelial dysfunction which causes hemolysis and platelet aggregation. The purpose of this research is to determine differences in platelet count and lactate dehydrogenase in early onset with late onset severe preeclampsia in Ulin Hospital Banjarmasin on January-December 2018 period. This research used analytic observational. The study sample was selected by non-probability sampling with a purposive sampling method, found 192 patients who fit the inclusion criteria. The data were analyzed using the Mann-Whitney test. The results showed that the median and percentile platelet counts of early onset severe preeclampsia were 248.000 (33.000-49.000) /µL and late onset 286.000 (47.000-556.000) /µL. Median and percentile lactate dehydrogenase in early onset severe preeclampsia 653 (279-3966) U/L and late onset 499 (197-1949) U/L. The conclusion of the research was that there was a significant difference in the platelet count (p = 0.009) and lactate dehydrogenase (p = 0,000) in early onset with late onset severe preeclampsia in Ulin Hospital Banjarmasin on January-December 2018 period. Keywords: severe preeclampsia, platelet, dehydrogenase lactate, early onset, late onset. Abstrak: Preeklampsia merupakan permasalahan kegawatdaruratan di bidang obstetri yang mempengaruhi kesejahteraan ibu dan bayi. Berdasarkan onsetnya, preeklampsia dibagi menjadi early onset dan late onset. Patofisiologi preeklampsia disebabkan adanya disfungsi endotel yang menyebabkan terjadinya hemolisis dan agregasi trombosit. Tujuan penelitian ini untuk mengetahui perbedaan jumlah trombosit dan laktat dehidrogenase preeklampsia berat early onset dengan late onset di RSUD Ulin Banjarmasin periode Januari-Desember 2018. Rancangan penelitan ini adalah observasional analitik. Sampel penelitian dipilih secara non-probability sampling serta menggunakan metode purposive sampling, didapatkan 192 pasien yang sesuai kriteria inklusi. Analisis data menggunakan uji Mann-Whitney. Hasil penelitian didapatkan median dan persentil jumlah trombosit preeklampsia berat early onset 248.000 (33.000-494.000)/µL dan late onset 286.000 (47.000-556.000)/µL. Median dan persentil laktat dehidrogenase pada preeklampsia berat early onset 653 (279- 3966)U/L dan late onset 499 (197-1949)U/L. Kesimpulan penelitian adalah terdapat perbedaan secara bermakna pada jumlah trombosit (p = 0,009) dan laktat dehidrogenase (p = 0,000) pada preeklampsia berat early onset dengan late onset di RSUD Ulin Banjarmasin periode Januari-Desember 2018. Kata-kata kunci: preeklampsia berat, trombosit, laktat dehidrogenase, early onset, late onset